40Ar/39Ar dating of basic–felsic dikes in the Sulu Orogen, Shandong Peninsula, China: Evidence for the destruction of the southeastern North China Craton. (3rd February 2020) - Shi, Wenbei; Wang, Fei; Yang, Liekun; Wu, Lin; Zhang, Weibin; Wang, Yinzhi
Abstract : During the Early Cretaceous, the North China Craton (NCC) underwent dramatic lithospheric thinning and destruction, resulting in widespread granitic magmatism and lithospheric extension. The geochronology of basic–felsic dikes provides a unique perspective on a crustal‐extension event that was related to the NCC destruction. Previous studies usually used zircon U–Pb dating to constrain the time of dike emplacement. This method is limited in terms of dating basic dikes because the authigenic zircons are rare or absent. Additionally, recording later reheating events during multiple phases of extension that occurred in the NCC after the Mesozoic is impossible. Here, we present 40 Ar/ 39 Ar geochronological data for basic–felsic dikes in the Sulu Orogen, Shandong Peninsula, East China. Our results indicate that these dikes were emplaced between ca. 127 and 95 Ma, with only two felsic samples recording ages <100 Ma, suggesting that crust‐derived magmatism decreased after this time. Several of these dikes that were adjacent to faults also recorded a later Cretaceous reheating event, which may have been related to fault movement and magmatic activity in the deeper crust. Combined with previous research results, Cretaceous dike emplacement was contemporaneous with crustal extension and widespread magmatic activity, slightly later than the peak time of the NCC destruction, suggesting an intrinsic connection between the dikes' emplacement and NCC destruction. The crustal magma and tectonic activity are direct evidence of the craton destruction, so these age data constrain the timing of destruction in the southeastern portion of the NCC to approximately 95 Ma.